Regimes de desfolhação sobre a ciclagem de nitrogênio e produção da forragem em pastos consorciados - Gomes, Fernanda de Kássia (2015)
Defoliation frequencies of dossal managed in intermittent grazing may cause changes in the production, persistence and nitrogen cycling in mixed pastures. In this study, we aimed to define the management that optimizes the input and cycling of nitrogen, favoring greater production and forage intake in pastures containing Brachiaria brizantha cv. Marandu and Arachis pintoi cv. Mandobi. Four defoliation frequencies were tested, defined by variable time intervals for dossal reaches 90%, 95% and 100% light interception (LI) and a fixed interval of 42 days (42DF). The experiment was performed in completely randomized design. The forage weight (FW) of grass in pre-pasturing was greater in dossal at 100% and 95% LI. The N and FW accumulation in grasses was greater at 90% LI, while the N and FW accumulation in leguminous was greater at 42DF. The accumulation of N and leaf litter was greater in dossal at 42DF, as well as the accumulation of total N in the leaf litter. The accumulation of total N (FW + leaf litter) in grasses was greater in dossal at 90% LI, while in leguminous, was greater at 42DF. The content of crude protein in grasses and leguminous was greater in dossal at 42DF. There was greater production of microbial protein in animals that grazed forage from dossal at 90% and 95% LI, less in dossal at 100% LI, and intermediary in dossal at 42DF. The total dry matter intake (DMI) was greater in dossals at 95% and 90% LI. This was similar to those found in dossal at 42DF and 100% LI, which were lower. The DMI of leguminous and of total crude protein was lesser in dossal at 100% LI. The quantity of N in animal excrements was greater in dossal at 95% LI and 90% LI. In the urine, the quantity of N was greater in dossal at 100% LI and 95% LI, this, similar to those found in dossal at 42DF. The total N excreted was greater in dossal at 42DF and 90% LI. The disappearing rate of leaf litter was greater in dossal at 42DF. The N accumulated in the leaf litter + N excreted was greater in dossal at 42DF, intermediate in dossal at 90% LI and 100% LI and, this was equal to that found in dossal at 95% LI, which was lower. Dossal with greater defoliation frequency accumulated greater quantity of N, however, there is less DMI in these dossal. The crude protein intake was greater and, the excess of N was excreted through urine. The N cycling was greater in dossal at 100% LI, however, their lesser intake may affect the animal performance.